Inhibitor-protected amoxicillin with increased amoxicillin content and active ingredients ratio of 14:1: the use for treatment of community-acquired respiratory infections and ENT infections in children. Expert Council Resolution - Roman S. Kozlov; Alexander I. Sinopalnikov; Olga V. Zaitseva; Sergey K. Zyryanov; Elena Yu. Radzig; Elena P. Karpova; Svetlana V. Zaitseva; Evelina E. Lokshina; Olga U. Stetsyuk; Irina V. Andreeva (LLC "MEDIAFORMAT", 2021)
The meeting of Expert Council, which included representatives of leading Russian research and higher education medical institutions, took place in Moscow. The Council discussed approaches to therapy of respiratory tract infections and ENT infections in children considering the global increase in antimicrobial resistance of respiratory tract pathogens. Special attention was paid to the use of new dosage form of amoxicillin-clavulanate 14:1, as well as to defining the category of patients to whom it is advisable to prescribe the high-dose amoxicillin-clavulanate.